XMM‐Newton publication statistics. Issue 2 (February 2014) - Ness, J.‐U.; Parmar, A.N.; Valencic, L.A.; Smith, R.; Loiseau, N.; Salama, A.; Ehle, M.; Schartel, N.
Abstract We assessed the scientific productivity of XMM‐Newton by examining XMM‐Newton publications and data usage statistics. We analyse 3272 refereed papers, published until the end of 2012, that directly use XMM‐Newton data. The SAO/NASA Astrophysics Data System (ADS) was used to provide additional information on each paper including the number of citations. For each paper, the XMM‐Newton observation identifiers and instruments used to provide the scientific results were determined. The identifiers were used to access the XMM‐Newton Science Archive (XSA) to provide detailed information on the observations themselves and on the original proposals. The information obtained from these sources was then combined to allow the scientific productivity of the mission to be assessed. Since around three years after the launch of XMM‐Newton there have been around 300 refereed papers per year that directly use XMM‐Newton data. After more than 13 years in operation, this rate shows no evidence that it is decreasing. Since 2002, around 100 scientists per year become lead authors for the first time on a refereed paper which directly uses XMM‐Newton data. Each refereed XMM‐Newton paper receives around four citations per year in the first few years with a long‐term citation rate of three citations per year, more than five years after publication. About half of the articles citing XMM‐Newton articles are not primarily X‐ray observational papers. The distribution of elapsed time between observations taken under the Guest Observer programme and first article peaks at 2 years with a possible second peak at 3.25 years. Observations taken under the Target of Opportunity programme are published significantly faster, after one year on average. The fraction of science time taken until the end of 2009 that has been used in at least one article is ∼90%. Most observations were used more than once, yielding on average a factor of two in usage on available observing time per year. About 20 % of all slew observations have been used in publications. The scientific productivity of XMM‐Newton measured by the publication rate, number of new authors and citation rate, remains extremely high with no evidence that it is decreasing after more than 13 years of operations.